Reinterpreting Iddah for Career Women: Najmuddin Tufi’s Maqashid Sharia Approach - Muslim, Nur Aziz; Taeali, Asman; Renaldi, Frisna Septian (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2024)
This study aims to reinterpret the concept of iddah (waiting period) for career women using a maqashid sharia approach based on Najmuddin Thufi’s thought. Iddah is an Islamic ruling intended to protect family and societal welfare, yet it presents challenges for modern career women. The traditional rules of iddah, which restrict activities outside the home, can impact women’s social and economic well-being, particularly for those who work. This research employs Najmuddin Thufi’s approach, which emphasizes public interest (maslahah), to explore whether the rules of iddah require adjustment for career women without compromising the fundamental objectives of Islamic law. Using a qualitative methodology with a library research approach, this study gathers data from literature on Islamic law, maqashid sharia and Najmuddin Thufi’s theory. The study finds that reconstructing iddah for career women is feasible by applying maqashid sharia principles, particularly through Thufi’s emphasis on maslahah. In the context of working women, traditional iddah rules—which limit activities outside the home—present challenges, especially concerning economic and social well-being. Based on the principle of maslahah, the iddah rule can be adapted without disregarding the core objectives of sharia, allowing career women to continue working during the waiting period as long as they uphold personal dignity and adhere to Islamic legal regulations. This approach offers a contextual and adaptive interpretation of Islamic law that aligns with modern developments while preserving the objectives of Sharia. The study concludes that iddah for career women can be reconstructed to bridge the gap between religious obligations and contemporary socio-economic needs.